2018
DOI: 10.1108/ijoa-11-2016-1082
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of demographic characteristics and certain psychological factors on the job embeddedness – turnover relationship among Thai health-care employees

Abstract: Purpose This paper aims to investigate the roles of demographic characteristics (i.e. generations and organizational tenure) and psychological factors (i.e. leader-member exchange and self-efficacy) as moderators of the relationship between job embeddedness and turnover intention, and the mediating effect of turnover intention between job embeddedness and actual turnover. Design/methodology/approach Data were collected from 422 health-care workers through a questionnaire survey and analyzed by means of a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 59 publications
3
23
0
1
Order By: Relevance
“…The result can be concluded that there is a negative correlation between job embeddedness and voluntary turnover. This is consistent with the study stated that there was a negative and significant relationship between job embeddedness and voluntary turnover (Afsar et al, 2018;Dechawatanapaisal, 2018;Coetzer et al, 2019). Karatepe and Ngeche (2012) studied about job embeddedness, turnover intention and job performance.…”
Section: Relationship Between Job Embeddedness and Voluntary Turnoversupporting
confidence: 89%
See 1 more Smart Citation
“…The result can be concluded that there is a negative correlation between job embeddedness and voluntary turnover. This is consistent with the study stated that there was a negative and significant relationship between job embeddedness and voluntary turnover (Afsar et al, 2018;Dechawatanapaisal, 2018;Coetzer et al, 2019). Karatepe and Ngeche (2012) studied about job embeddedness, turnover intention and job performance.…”
Section: Relationship Between Job Embeddedness and Voluntary Turnoversupporting
confidence: 89%
“…Job embeddedness is one of the strategies that has been proven to be able to influence voluntary turnover. Dechawatanapaisal (2018) states that there is a negative relationship between job embeddedness and turnover intention.…”
Section: Relationship Between Job Embeddedness and Voluntary Turnovermentioning
confidence: 99%
“…On the other hand, if the community networks are strong then the perceived costs of leaving the current job would increase (Holtom et al, 2019). There are some evidences showing that if the perception of leaving the community is difficult then it is more difficult to quit a current job (Dechawatanapaisal, 2018b). Therefore, this study strongly argued that community-embeddedness is linked with the VTOI among young teachers.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 67%
“…Similarly, organizational-and community-embeddedness affect the decisions related to VTOI in academics (Dechawatanapaisal, 2018b). Recently, a study conducted in the Iranian education sector revealed that organizational practices sometimes have an adverse effect on turnover if teachers perceive organizational support is low.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 99%
See 1 more Smart Citation